Stability and change at Çadır Höyük in central Anatolia: a case of Late Chalcolithic globalisation?. (2019) - Steadman, Sharon R.; McMahon, Gregory; Arbuckle, Benjamin S.; von Baeyer, Madelynn; Smith, Alexia; Yıldırım, Burcu; Hackley, Laurel D.; Selover, Stephanie; Spagni, Stefano
Abstract: Scholars have recently investigated the efficacy of applying globalisation models to ancient cultures such as the fourth-millennium BC Mesopotamian Uruk system. Embedded within globalisation models is the 'complex connectivity' that brings disparate regions together into a singular world. In the fourth millennium BC, the site of Çadır Höyük on the north-central Anatolian plateau experienced dramatic changes in its material culture and architectural assemblages, which in turn reflect new socio-economic, sociopolitical and ritual patterns at this rural agro-pastoral settlement. This study examines the complex connectivities of the ancient Uruk system, encompassing settlements in more consistent contact with the Uruk system such as Arslantepe in southeastern Anatolia, and how these may have fostered exchange networks that reached far beyond the Uruk 'global world' and onto the Anatolian plateau.